Peningkatan Literasi Keuangan dan Pencatatan Akuntansi Sederhana bagi UMKM di Desa Pesisir untuk Mendorong Keberlanjutan Usaha Studi di Kelurahan Mangkang Wetan, Kecamatan Tugu, Kota Semarang: Pengabdian - Nadia Dwi Irmadiani; Hermawan Budiyanto; Alya Takwarina Cahyani; Maliki Aji Prakoso; Slamet Riyono (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Micro, small, and medium enterprises (MSMEs) in coastal areas generally face challenges in managing business finances effectively due to low financial literacy and the absence of simple accounting records. This community service program aims to improve financial literacy and daily financial recording skills among MSMEs in Mangkang Wetan Subdistrict, Tugu District, Semarang City. The method used is Participatory Action Research (PAR) through a participatory training approach and field assistance. The activities include problem identification, training sessions, recording simulations, and field visits over a two-week period. Evaluation results show that participants experienced an average score increase of 43.2% from pre-test to post-test in terms of financial literacy understanding. A total of 64% of participants began independently recording their daily finances. In addition to improved knowledge and skills, there was also a shift in attitudes regarding the importance of financial record-keeping and the emergence of initiatives to share this good practice with fellow entrepreneurs. Challenges such as low consistency and limited digital access remain concerns in ensuring program sustainability. Therefore, synergy between academics, the government, and local communities is needed to create a sustainable and inclusive financial literacy ecosystem.